Case Series on Ochronotic Arthropathy: An Incidental Finding in Osteoarthritis Hip, Review of Literature - A, Kavitha; V, Kavita; Kar, Shreya (Annals of Pathology and Laboratory Medicine, 2023)
Ochronotic arthropathy, an infrequent ailment characterized by the buildup of oxidized and polymerized metabolites of homogentisic acid, presents a distinctive challenge in the medical realm. The affinity of homogentisic acid for collagen, a vital constituent of connective tissues, underpins the pathogenesis of this condition. Joints, crucial components of the body's architecture, become the primary focus of this disorder. Invariably, the axial spine joints are its initial target, followed by a subsequent involvement of the knees, shoulders, and hips, ultimately ushering in degenerative transformations. The objective of this article is to cast a spotlight on the infrequently encountered ochronotic arthropathy, with specific emphasis on its manifestation in the femoral head. This report showcases two incidental cases wherein the head of the femur becomes an unforeseen site of affliction. The intricacies of ochronotic arthropathy extend beyond its rarity, as it challenges conventional understanding and diagnostic approaches. By examining its manifestation within the femoral head, we strive to unravel the nuances of its impact on this particular joint. This exploration not only expands our comprehension of the condition itself but also underscores the critical importance of recognizing its potential to manifest in atypical locations. As medical practitioners, a deeper understanding of such unconventional occurrences equips us to better diagnose, manage, and treat ochronotic arthropathy, ultimately enhancing patient care and outcomes.